Keramahtamahan Mendatangkan Berkat: Tinjauan Teologis atas Kejadian 18:1-15 dalam Perspektif Paus Fransiskus di Ensiklik Fratelli Tutti - Heribertus Pius Buto; Robertus Mirsel (JURNAL PASTORAL KATEKETIK, 2025)
This article aims to examine the extent to which hospitality can bring blessings in perspective Pope Francis’ Encyclical Fratelli Tutti, as demonstrated by the experience of Abraham and Sarah in Genesis 18:1-15. The text recounts an encounter between Abraham and three men who came to him. This encounter took place near the cedar tree at Mamre, where Abraham showed his hospitality through two gestures and a good meal. At the end of the encounter, the visitors unexpectedly promised that Abraham would have offspring. This article uses a narrative approach to highlight the patterns and techniques of hospitality that bring blessings. The author emphasizes how Abraham's hospitality changed his life and brought unexpected blessings. Through this approach, the author concludes that hospitality is an act that springs from Abraham's heart, demonstrated through his attentiveness to his guests and his loving acceptance and hospitality towards strangers. In line with the voice of the Catholic Church in the Pope Francis’ Encyclical Fratelli Tutti, hospitality is the foundation of brotherhood and friendship in life together.